Degradation of catecholate, hydroxamate, and carboxylate model siderophores by extracellular enzymes - Chinazam Emmanuel Chukwuma; Owen William Duckworth; Oliver Baars (PLoS ONE, 2025)
Siderophores are low-molecular weight biomolecules with a high affinity for ferric iron (FeIII) that can impact plant and microbial growth. Although their formation and biology have been investigated in detail, little is known about the environmental fate of siderophores, including their potential reactions with common degradative enzymes, which may influence or hinder the ability to promote the uptake of Fe for plants and microbes. In this study, we examined the ability of the model extracellular enzymes phenol oxidase, protease, and horseradish peroxidase to degrade apo siderophores and FeIII siderophore complexes. The siderophores were selected to represent the natural diversity of siderophore structures: the bacterial triscatecholamide siderophore protochelin; the bacterial trishydroxamate siderophore desferrioxamine B (DFOB); and the synthetic carboxylate phytosiderophore analog proline-2′-deoxymugineic acid (PDMA). In general, apo siderophores were more susceptible to degradation, with some protection of the siderophore provided by FeIII complexation. Phenol oxidase reacted rapidly with protochelin, leading to 90% degradation of protochelin after 24 hours of reaction, which could be modeled by Michaelis-Menten kinetics. Peroxidases in the presence of H2O2 were also effective in the degradation of protochelin (80%) and, to a lesser extent, reacted with DFOB, leading to ~5% degradation. Control experiments showed that protochelin oxidation is caused primarily by H2O2 alone, even in the absence of the peroxidase enzyme. When bound to FeIII, the degradation of protochelin by phenol oxidase and DFOB degradation by peroxidase was reduced by ~50% and ~3%, respectively. No significant reaction was detected between PDMA and any of the three enzymes, supporting its proposed use for plant Fe fertilization.